2015
DOI: 10.1002/chem.201500385
|View full text |Cite
|
Sign up to set email alerts
|

Mononuclear Polypyridylruthenium(II) Complexes with High Membrane Permeability in Gram‐Negative Bacteria—in particular Pseudomonas aeruginosa

Abstract: Ruthenium(II) complexes containing the tetradentate ligand bis[4(4'-methyl-2,2'-bipyridyl)]-1,n-alkane ("bbn "; n=10 and 12) have been synthesised and their geometric isomers separated. All [Ru(phen)(bbn )](2+) (phen=1,10-phenanthroline) complexes exhibited excellent activity against Gram-positive bacteria, but only the cis-α-[Ru(phen)(bb12 )](2+) species showed good activity against Gram-negative species. In particular, the cis-α-[Ru(phen)(bb12 )](2+) complex was two to four times more active than the cis-β-[… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 33 publications
2
27
0
Order By: Relevance
“…The emission of the complexes was detected after only one minute of dosing at room temperature (Supporting Information, Video 1). This extremely fast cellular uptake is remarkable, if one considers that previously reported protocols involve incubation times from 30 minutes up to two hours . All the complexes were excited with a 405 nm laser and the emission collected in the 500–700 nm region (see the Supporting Information), consistent with the emission properties of the complexes in aqueous media (Table S1, Supporting Information).…”
Section: Figuresupporting
confidence: 62%
See 2 more Smart Citations
“…The emission of the complexes was detected after only one minute of dosing at room temperature (Supporting Information, Video 1). This extremely fast cellular uptake is remarkable, if one considers that previously reported protocols involve incubation times from 30 minutes up to two hours . All the complexes were excited with a 405 nm laser and the emission collected in the 500–700 nm region (see the Supporting Information), consistent with the emission properties of the complexes in aqueous media (Table S1, Supporting Information).…”
Section: Figuresupporting
confidence: 62%
“…This extremelyf ast cellular uptake is remarkable, if one considers that previously reported protocols involve incubation times from 30 minutes up to two hours. [14,26,27] All the complexes were excited with a4 05 nm laser and the emission collected in the 500-700nmr egion (see the Supporting Information), consistent with the emission properties of the complexes in aqueous media (Table S1, SupportingI nformation). Acquisition of z-stack images confirmed that the complexes were effectively internalised within the live bacteria and were not interacting with the outer side of the membrane (see the Supporting Information, Video 2).…”
supporting
confidence: 54%
See 1 more Smart Citation
“…The synthesis of the [Ru(bb 7 )(dppz)] 2+ complex containing the flexible bb 7 ligand is presented in Scheme . To avoid the formation of the dinuclear complex, the [Ru(bb 7 )(dppz)] 2+ was synthesised by direct reaction of bb 7 with the appropriate mole ratio of the precursor complex cis , cis ‐[RuCl 2 (dmso) 2 (dppz)] (dmso=dimethyl sulfoxide) in ethylene glycol as previously reported . The [Ru(bb 7 )(dppz)] 2+ complex was purified by SP Sephadex C‐25 cation‐exchange chromatography.…”
Section: Resultsmentioning
confidence: 99%
“…The [Ru(bb 7 )(dppz)] 2+ complex was characterised by microanalysis, NMR spectroscopy and high‐resolution electrospray ionisation (ESI) mass spectrometry. The [Ru(bb 7 )(dppz)] 2+ complex displayed a resolvable 1 H NMR spectrum, and all proton chemical shifts were assigned based on the comparison with those of similar compounds . Only one symmetrical set of resonances was observed for both the dppz and bb 7 aromatic protons.…”
Section: Resultsmentioning
confidence: 99%